Causality between Green Stock Market with Monetary Policy, Global Uncertainty, and Environmental Damage in Indonesia - Sakuntala, Dwita; Majid, M. Shabri Abd.; Aliasuddin, Aliasuddin; Suriani, Suriani (International Journal of Energy Economics and Policy, 2022)
The study examines the effect of monetary policy, global uncertainty and environmental damage on the green stock market in Indonesia in the long and short term, using the Autoregressive Distributed Lag (ARDL) bound test method. The ARDL bound test results show that there is cointegration in the long term between the green stock market and monetary policy, global uncertainty and environmental damage. Empirical evidence finds that in the long term, the variables that affect the green stock market in Indonesia are monetary policy from interest rates, global uncertainty and environmental damage from carbon emissions. While in the short term the variables that affect the green stock market are interest rates without lag, lag 1, lag 2 and lag 3; global uncertainty in lag 1 and lag 2; and carbon emissions without lag and lag 1; while forest damage without lag shows a very weak effect at the 10% significance level. Coefficient also shows significant and negative sign. A deeper analysis found that there is a bidirectional causality from monetary policy to green stock markets and vice versa, and from carbon emissions to green stock markets and vice versa.